The Formation of Authigenic Carbonates at a Methane Seep Site in the Northern Part of the Laptev Sea - Alexey Ruban; Maxim Rudmin; Oleg Dudarev; Alexey Mazurov (Minerals, 2020)
Authigenic carbonates from cold seeps are unique archives for studying environmental conditions, including biogeochemical processes associated with methane-rich fluid migration through the sediment column. The aim of this research was to study major oxide, mineralogical, and stable isotopic compositions of cold-seep authigenic carbonates collected in the northern part of the Laptev Sea. These carbonates are represented by Mg-calcite with an Mg content of 2% to 8%. The δ13C values range from −27.5‰ to −28.2‰ Vienna Peedee belemnite (VPDB) and indicate that carbonates formed due to anaerobic oxidation of methane, most likely thermogenic in origin. The authigenic pyrite in Mg-calcite is evidence of sulfate reduction during carbonate precipitation. The δ18O values of carbonates vary from 3.5‰ to 3.8‰ VPDB. The calculated δ18Ofluid values show that pore water temperature for precipitated Mg-calcite was comparable to bottom seawater temperature. The presence of authigenic carbonate in the upper horizons of sediments suggests that the sulfate–methane transition zone is shallowly below the sediment–water interface.